Babesiosis Occurrence among the Elderly in the United States, as Recorded in Large Medicare Databases during 2006–2013 - Menis, Mikhail (PLoS One, 2015)
BACKGROUND: Human babesiosis, caused by intraerythrocytic protozoan parasites, can be an asymptomatic or mild-to-severe disease that may be fatal. The study objective was to assess babesiosis occurrence among the U.S. elderly Medicare beneficiaries, ages 65 and older, during 2006–2013. METHODS: Our retrospective claims-based study utilized large Medicare administrative databases. Babesiosis occurrence was ascertained by recorded ICD-9-CM diagnosis code. The study assessed babesiosis occurrence rates (per 100,000 elderly Medicare beneficiaries) overall and by year, age, gender, race, state of residence, and diagnosis months. RESULTS: A total of 10,305 elderly Medicare beneficiaries had a recorded babesiosis diagnosis during the eight-year study period, for an overall rate of about 5 per 100,000 persons. Study results showed a significant increase in babesiosis occurrence over time (p<0.05), with the largest number of cases recorded in 2013 (N = 1,848) and the highest rates (per 100,000) in five Northeastern states: Connecticut (46), Massachusetts (45), Rhode Island (42), New York (27), and New Jersey (14). About 75% of all cases were diagnosed from May through October. Babesiosis occurrence was significantly higher among males vs. females and whites vs. non-whites. CONCLUSION: Our study reveals increasing babesiosis occurrence among the U.S. elderly during 2006–2013, with highest rates in the babesiosis-endemic states. The study also shows variation in babesiosis occurrence by age, gender, race, state of residence, and diagnosis months. Overall, our study highlights the importance of large administrative databases in assessing the occurrence of emerging infections in the United States.